Alcohol and pregnenolone interaction on cerebral arteries through targeting of vascular smooth muscle Ca2+- and voltage-gated K+ channels of big conductance - Kelsey C. North; Andrew A. Shaw; Luiz Moreira; Anna N. Bukiya; Alex M. Dopico (Frontiers Media S.A., 2023)
Despite the significant number of people who may be taking pregnenolone supplements while drinking alcohol (ethanol), the widely documented cerebrovascular actions of pregnenolone and ethanol, and the critical dependence of cerebrovascular function on cerebral artery diameter, there are no studies addressing the effect of pregnenolone + ethanol in combination on cerebral artery diameter. We investigated this by evaluating the effect of this combination on middle cerebral artery diameter in male and female C57BL/6J mice, both in vivo and in vitro. The use of de-endothelialized, in vitro pressurized middle cerebral artery segments allowed us to conduct a concentration-response study of constriction induced by pregnenolone ± ethanol, in which drug action could be evaluated independently of circulating and endothelial factors. In both male and female animals, pregnenolone at lower concentrations (≤1 µM) was found to synergize with 50 mM ethanol to cause vasoconstriction. In both sexes, this synergism was lost as one or both vasoconstrictors approached their maximally effective concentrations (75 mM and 10 µM for ethanol and pregnenolone, respectively), whether this was evaluated in vitro or in vivo using a cranial window. Vasoconstriction by pregnenolone + ethanol was abolished by 1 µM paxilline, indicating BK channel involvement. Moreover, cell-free recordings of BK channel activity in cerebral artery myocyte membranes showed that 10 µM pregnenolone and pregnenolone +50 mM ethanol reduced channel activity to an identical extent, suggesting that these drugs inhibit cerebrovascular BK channels via a common mechanism or mechanisms. Indeed, pregnenolone was found to disrupt allosteric coupling to Ca2+-driven gating, as previously reported for ethanol.